A poesia de Paulo Leminski: limiar, humor, ruína - Passos, Lucas dos (2012)
The readings commonly made on the poetic works by Paulo Leminski mainly (or just) regard their intertextual potentials claiming traditions that, as the concrete poetry, this native of Curitiba intended to convey. However, when stop in this point, this kind of interpretation can distort the tense relation established between this poetry and its historical context, set up at the beginning of the 60s, going through the military dictatorship until the turbulent re-democratization process in the 80s. The aim is therefore to review part of Leminski s bibliography intending to more clearly detect this interpretative gap and to analyze Leminki s poems in the midst of a time of turmoil. For that, some of fundamental notions of Walter Benjamin s thoughts will come up history, ruin and threshold , being nevertheless and not rarely interlinked with issues on the study of poetry and of wit (by Freud), building the dynamic prism that Leminski s aesthetics demands.